Uncertainty quantification in littoral erosion. (17th January 2017) - Mohammadi, Bijan
Highlights: Value at Risk (VaR) of bed flow receptivity for extreme deformation scenarios. Gaussian framework where VaR and variance are easily linked. Dynamics of variance of PDF of bed receptivity linked to bottom morphodynamics. Bed deformations minimizing given functional. Uncertainty accounted for during the fluid-structure coupling. Abstract: We aim at quantifying the impact of flow state uncertainties in littoral erosion to provide confidence bounds on deterministic predictions of bottom morphodynamics. Two constructions of the bathymetry standard deviation are discussed. The first construction involves directional quantile-based extreme scenarios using what is known on the flow state Probability Density Function (PDF) from on site observations. We compare this construction to a second cumulative one using the gradient by adjoint of a functional involving the energy of the system. These ingredients are illustrated for two models for the interaction between a soft bed and a flow in a shallow domain. Our aim is to keep the computational complexity comparable to the deterministic simulations taking advantage of what already available in our simulation toolbox.